2022
DOI: 10.3390/jof8070678
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Candidemia in Patients with COVID-19 Admitted to Five ICUs in France

Abstract: Whether severe COVID-19 is by itself a significant risk factor for the development of candidemia currently remains an open question as conflicting results have been published. We aim to assess the occurrence of candidemia in patients with severe COVID-19 admitted to the intensive care unit (ICU). We conducted a retrospective study on patients with severe SARS-CoV-2-related pneumonia admitted to 5 ICUs in France who were specifically screened for fungal complications between March 2020 and January 2021. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…In the present study, the total incidence of fungal infections (10.7%), CAPA (7.86%), and CAC (3.37%) were similar to those already described in the literature [ 1 , 10 , 12 , 13 , 14 ]. It is also noteworthy that in the subgroup of ECMO patients, fungal infections were far more common (6/11, 54.5%).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the total incidence of fungal infections (10.7%), CAPA (7.86%), and CAC (3.37%) were similar to those already described in the literature [ 1 , 10 , 12 , 13 , 14 ]. It is also noteworthy that in the subgroup of ECMO patients, fungal infections were far more common (6/11, 54.5%).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it remains fairly unclear whether the excess mortality observed in patients diagnosed with CAPA should be attributed to CAPA per se or to the co-existence of other risk factors potentially driving both vulnerability to CAPA and a high all-cause ICU mortality rate [ 18 ]. Recent data on CAC show that patients with CAC might not have differences in mortality [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Otherwise, these techniques pose a significant challenge due to some limitations. A French retrospective study reported that BDG testing lacked sufficient sensitivity and specificity when performed on sera collected from patients with severe COVID-19 admitted to the ICU ( 102 ). Serum BDG testing has been broadly used in COVID-19 patients for the detection of CAPA in developed countries, in contrast to not being available in developing countries ( 103 ).…”
Section: Fungal Co-infections In Covid-19 Patientsmentioning
confidence: 99%